Sustainable biodiesel production from Delonix regia pods: Advancing renewable energy through pyrolytic oil and dual-pathway esterification - Subramanian, Sudagar; Rajendran, Silambarasan; Keçebaş, Ali; Alwetaishi, Mamdooh; Bahuruteen Ali Ahamadu, H.; Munimathan, Arunkumar; Fayaz, H. (Institution of Chemical Engineers, 2025)
This study investigates the production of biodiesel from pyrolytic oil obtained from Delonix regia pods (DRP), a novel biomass feedstock underutilized in renewable energy research. The research employs a dual-pathway esterification approach, utilizing methanol (methanolysis) and ethanol (ethanolysis) to optimize biodiesel production. Pyrolysis of 100 g DRP at 450 °C yielded 41 g bio-oil. From this, 250 mL of oil was processed into 200 mL methyl ester (MB20) and 190 mL ethyl ester (EB20), corresponding to biodiesel yields of 17.4 % and 16.6 % (g/g DRP), respectively. Comparative analysis revealed that MB20 outperformed EB20 in critical fuel properties and engine performance. MB20 exhibited a viscosity of 2.8 cSt and a heating value of 40.25 MJ/kg, surpassing EB20’s viscosity of 3.2 cSt and heating value of 39.65 MJ/kg. Engine tests demonstrated a 2 % higher brake thermal efficiency for MB20 compared to EB20, along with a significant reduction in emissions—NOx (654 ppm), CO (0.17 %), and HC (34 ppm)—making MB20 a more sustainable and efficient alternative and also shows that MB20 blends has closer fuel properties of diesel and thus MB20 blends has closer BTE and lower emission than diesel. The study further demonstrated the superior oxidative and thermal stability of MB20, evidenced by an 11 % lower viscosity increase during storage compared to EB20, highlighting its potential as a viable alternative to conventional diesel without requiring engine modifications. This study addresses the scientific niche of utilizing underexplored biomass feedstocks like DRP for sustainable biodiesel production, contributing to the optimization of renewable energy technologies. Future research should focus on scaling up production, optimizing reactor designs, and enhancing economic feasibility to support global energy sustainability goals.